Ploidy level studies on the Dioscorea cayenensis/Dioscorea rotundata complex core set - Obidiegwu, J.E.; Loureiro, J.; Ene-Obong, E.E.; Rodríguez, E.; Kolesnikova-Allen, M.; Santos, C.; Muoneke, C.; Asiedu, Robert (Springer, 2009)
The Guinea yams, Dioscorea cayenensis Lam. and D. rotundata Poir. (D. cayenensis–D. rotundata complex), represent a highly importantcrop, widely distributed in the humid and semi-humidtropics. The ploidy levels of 170 accessions of the core set of Guinea yams from West African countries was determined using flow cytometry with propidium iodide staining. One hundred and eight of the genotypes were found to be tetraploid, 47 were hexaploid and five were octoploid. One mixoploid individual containing tetraploid and hexaploid nucleiwas also detected. A deeper analysis considering each separate taxon revealed that while for D. rotundata the majority of individuals were tetraploid, for D. cayenensis this ploidy level was not detected in any of the accessions. Also, no association between ploidy level and place of cultivation was found for the evaluated germplasm. The obtained data is highly valuable for breeding programs of Guinea yam, especially for the optimization of future hybridization experiments directed to the genetic improvement of this economically important crop